ENVIRONMENT MANAGEMENT IN STUDENTS HIGHER EDUCATION - Vladimirov, Lyubomir; Kovachev, Nikolai; Manev, Plamen; Vladimirov, Vladimir (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The purpose of the work is in taking appropriate training themes for the educational level of qualification "bachelor". The main research directions are: 1) Definition of the purpose and objectives of training, 2) Substantiation of the major themes in education, 3) Formulation of topics and methodology for conducting exercises to achieve the necessary practical training, 4) Development of technology training.